Penampilan Fenotipik, Variabilitas, dan Heritabilitas 32 Genotipe Cabai Merah Berdaya Hasil Tinggi - Qosim, Warid Ali; Rachmadi, Meddy; Hamdan, Jajang Sauman i; Nuri, Ihsanudin (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2013)
Information of phenotypic performance, genetic variability and heritability estimation are very important to improve the yield of red pepper. The aims of this research was to obtain the information on the phenotypic performance, variability and heritability of 32 high yielding genotypes of red pepper. The experiment was arranged in randomized complete block design in which 32 genotypes of red pepper were used as a treatment. The results showed that the genotypes of BPH 0604, KRT 2, RMCK I, RMCK II, and UPKRT I 99 performed better than others in the fruit characters such as number of fruits per plant, number of fruit per plot, weight per fruit, fruit weight per plant, fruit weight per plot. The genetic and phenotypic variability were considerably wide for characters such as plant height, flowering time, stem diameter, leaf width, length of peduncle, petiole length, fruit diameter, number of fruits per plant, number of fruit per plot, and weight per fruit. Heritability estimation of plant height, flowering time, stem diameter, fruit diameter, number of fruits per plant, number of fruit per plot, weight per fruit, fruit weight per plant and fruit weight per plot were high.Keyword: Capsicum annuum, genetic material, high yielding variety, plant breeding